Impact of Depleting Therapeutic Monoclonal Antibodies on the Host Adaptive Immunity: A Bonus or a Malus? - Deligne, Claire; Milcent, Benoît; Josseaume, Nathalie; Teillaud, Jean-Luc; Sibéril, Sophie (Frontiers in Immunology, 2017)
Clinical responses to anti-tumor monoclonal antibody (mAb) treatment have been regarded for many years only as a consequence of the ability of mAbs to destroy tumor cells by innate immune effector mechanisms. More recently, it has been also shown that anti-tumor antibodies can induce a long-lasting anti-tumor adaptive immunity, likely responsible for durable clinical responses, a phenomenon that has been termed the vaccinal effect of antibodies. However, some of these anti-tumor antibodies are directed against molecules expressed both by tumor cells and normal immune cells, in particular lymphocytes, and, hence, can also strongly affect the host adaptive immunity. In addition to a delayed recovery of target cells, lymphocyte depleting-mAb treatments can have dramatic consequences on the adaptive immune cell network, its rebound, and its functional capacities. Thus, in this review, we will not only discuss the mAb-induced vaccinal effect that has emerged from experimental pre-clinical studies and clinical trials, but also the multifaceted impact of lymphocytes-depleting therapeutic antibodies on the host adaptive immunity. We will also discuss some of the molecular and cellular mechanisms of action whereby therapeutic mAbs induce a long-term protective anti-tumor effect and the relationship between the mAb-induced vaccinal effect and the immune response against self-antigens.